Mua (HP0868) Is a Nickel-Binding Protein That Modulates Urease Activity in Helicobacter pylori - Stéphane L. Benoit (American Society for Microbiology, 2011)
ABSTRACT A novel mechanism aimed at controlling urease expression in Helicobacter pylori in the presence of ample nickel is described. Higher urease activities were observed in an hp0868 mutant (than in the wild type) in cells supplemented with nickel, suggesting that the HP0868 protein (herein named Mua for modulator of urease activity) represses urease activity when nickel concentrations are ample. The increase in urease activity in the Δmua mutant was linked to an increase in urease transcription and synthesis, as shown by quantitative real-time PCR, SDS-PAGE, and immunoblotting against UreAB. Increased urease synthesis was also detected in a Δmua ΔnikR double mutant strain. The Δmua mutant was more sensitive to nickel toxicity but more resistant to acid challenge than was the wild-type strain. Pure Mua protein binds 2 moles of Ni2+ per mole of dimer. Electrophoretic mobility shift assays did not reveal any binding of Mua to the ureA promoter or other selected promoters (nikR, arsRS, 5′ ureB-sRNAp). Previous yeast two-hybrid studies indicated that Mua and RpoD may interact; however, only a weak interaction was detected via cross-linking with pure components and this could not be verified by another approach. There was no significant difference in the intracellular nickel level between wild-type and mua mutant cells. Taken together, our results suggest the HP0868 gene product represses urease transcription when nickel levels are high through an as-yet-uncharacterized mechanism, thus counterbalancing the well-described NikR-mediated activation. IMPORTANCE Urease is a nickel-containing enzyme that buffers both the cytoplasm and the periplasm of Helicobacter pylori by converting urea into ammonia and carbon dioxide. The enzyme is the most abundant protein in H. pylori, accounting for an estimated 10% of the total protein content of the cell, and it is essential for early colonization and virulence. Numerous studies have focused on the transcription of the structural ureAB genes and its control by the regulatory proteins NikR and ArsR. Here we propose that urease transcription is under the control of another Ni-binding protein besides NikR, the Mua (HP0868) protein. Our results suggest that the Mua protein represses urease transcription when nickel levels are high. This mechanism would counterbalance the NikR-mediated activation of urease and ensure that, in the presence of a high nickel concentration, urease activation is limited and does not lead to massive production of detrimental ammonia.